Responsibilities of Supervisor and Officers Who Commit Violations Under the Officer Violable Responsibility Act, B.E. 2539 - Mainthaisong, Naruephol (Journal of Graduate MCU KhonKaen Campus, 2022)
In case of the officer commits and offense against a government agency by dishonestly and embezzling money may not be regarded as a violation in the performance of duties. It is an act that takes advantage of the opportunity that one’s duties as a financial officer misappropriate the money. So the offending officer would not be in a condition to be protected under section 8 of the Official Infringement Acceptance Act, B.E. 2539(1996). Which the state agency cannot issue and order requiring the officials to make payment to the state agency. But government agencies must sue the officials as a case to the Court of justice. The official is personally liable in full under the provisions of the Civil and Commercial Code. As for the officers who are in command be an officer in the act of performing duties from the exercise of legal powers or neglecting to perform duties as required by the law which the waste is a defect in performing duties. Their actions will be protected by law. If the officer has inspected enough without being neglected does not monitor the work of the financial officer at all and is deemed to be impaired by negligence in the performance of duties, without being serious. The commanding officer is not liable to pay compensation under the provisions of Section 8 of the Officers’ Violable Responsibility Act, B.E.2539